Maimónides y la teoría política dialéctica - Roiz, Javier (Foro Interno, 2006)
Maimonides understood politics to be a matter of who commands and who is to obey these commands, and of how to get rid of corruption. He was thoroughly versed in Aristotle’s teachings, but then took his political thinking well beyond the limits of the Greek philosophical tradition. Living between two religious and political giants led him to reflect on the concepts of “emet”, truth, and “shalom”, peace, and on the relationship between the religious beliefs and the moral qualities that build a city. The science of politics is concerned with government, and begins with the issue of governing one’s own individual life. As a doctor and rabbi, he took into account both body and soul while addressing in a new fashion the relationship between knowledge and power.